Demam Berdarah Dengue Analisis Pola Persebaran Kejadian Demam Berdarah Dengue Di Kota Pekanbaru Tahun 2020 - Eggy Arya Giofandi (Jurnal Kependudukan dan Pembangunan Lingkungan, 2021)
Infectious diseases are one of the health problems that have not been optimally addressed, this can be seen from the high increase in the number of cases in the western part of the country. The purpose of this study was to determine the pattern of distribution of dengue hemorrhagic fever in Pekanbaru City. The method used in this study is the nearest neighbor analysis method with calculations from incident data which are assumed to be from the coordinates of the incident location. Information obtained during the study showed cases of dengue hemorrhagic fever in 2020 reached 611 cases with the highest incidence area being in Payung Sekaki District with a total of 71 cases, then related to the distribution pattern of the incident, it has clustered patterns with the nearest neighbor analysis value ranging from 0.535 which the ratio of patients more dominant at the age of 6-11 years belonging to the category of childhood. The body's immune system is still immature in fighting various viral diseases because the body's ability in childhood is still vulnerable to infection.